Bioinspired Biopolymer Hydrogel Application to Improve Installation Efficiency and Load Carrying Capacity of Piles - Park, Suhyuk; Yum, Jun Hyeok; Lee, Minhyeong; Cho, Gye Chun; Lee, Sojeong; Chang, Ilhan (Geotechnical Special Publication, 2024)
Installation of urban piles presents a number of difficulties in terms of noise, vibration, and impact on adjacent structures. The environmentally friendly ground improvement technique known as “biopolymer-based soil treatment” (BPST) is being actively considered in both academic and real-world settings. It is expected that the shear thinning properties of biopolymer hydrogels lessen frictional resistance during pile movement. In addition, trivalent ion-induced crosslinking between soil particles and xanthan gum biopolymer hydrogel improves the interaction between the soil and the pile after pile installation. Through these properties, in this study, the pile skin resistance reduction and pullout resistance enhancement effects induced by biopolymer hydrogel injection and subsequent crosslinking have been assessed. The interface direct shear test was conducted to evaluate the interface shear behavior between sandpaper and soil/treated soil. The model pile was pulled out to evaluate the load carrying capacity of the pile. The load carrying capacity of the biopolymer-treated pile was the smallest. Also, piles in sand and crosslinked biopolymer-treated piles exhibited similar load-displacement curves, especially in the initial displacement. However, in the residual state, the resistance of the pile in the crosslinked biopolymer-treated sand was higher. Through the experimental results, the feasibility of applying biopolymer to increase installation efficiency is reviewed. In addition, it was found appropriate to use the crosslinking method to increase the load carrying capacity.
Keywords: Adjacent structures; Crosslinked; Frictional resistance; Ground improvement; Improvement technique; Noise impact; Property; Real world setting; Shear-thinning; Soil treatments